Gari, a Cassava (Manihot esculenta Crantz) Derived Product: Review on Its Quality and Their Determinants - Franklin Ngoualem Kégah; Robert Ndjouenkeu (Journal of Food Quality)
Gari or Tapioca or Rale, a roasted yellow or white granulated product found on market stalls of sub-Saharan African countries (SSA), is made from cassava through the successive steps of peeling, grating, fermentation and/or dewatering, and roasting, and is the most consumed cassava derived product. The strengthening of its value chain can contribute to food sovereignty as well as improve the lifestyle of many urban and rural dwellers of SSA. This strengthening of the Gari value chain requires the identification of its weaknesses and proposes research and development initiatives that will increase its contribution to food sovereignty. The present review aimed thus at achieving this goal through a review of up to now knowledge on (i) end-users preferences for cassava and Gari in SSA; (ii) the quality (nutritional and microbiological) of Gari found on market stalls; (iii) processing and raw material determinant of this quality; (iv) research and development trials which have been done to improve the nutritional quality of Gari. It also proposes some scientific challenges to overcome in SSA in order to have all the ingredients for success.